Pengaruh Struktur Kepemilikan Institusional, Ukuran Perusahaan dan Dividen Terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014 - Krisnando . (Jurnal Ekonomi, 2017)
This study aims to determine the effect of ownership structure, company size and dividend to earnings management in companies listed on the Indonesia Stock Exchange, partially and simultaneously. The population in this research is manufacturing companies listed in Indonesia Stock Exchange from 2010 to 2014. List of companies listed at this time amounted to 141 companies. Based on the sampling criteria obtained a total of 18 sample companies listed in Indonesia Stock Exchange 2010-2014. The data analysis method used is Testing Assumptions Classical (Normality Test, Multicollinearity Test, Heteroskedastisity Test and autocorrelation test), Multiple Linear Regression Analysis, Hypothesis Testing (Statistic t test and F test), as well as the Test Coefficient of Determination.From the results of the study concluded that 1) The ownership structure no significant effect on earnings management in companies listed on the Indonesia Stock Exchange, so ha1 not proven, 2) The size of the company a significant effect on earnings management in companies listed on the Indonesia Stock Exchange, so that Ha2 proven, 3) dividends significant effect on earnings management in companies listed on the Indonesia Stock Exchange, so HA3 proven, 4) the ownership structure, company size and dividend significantly influence earnings management in companies listed on the Indonesia Stock Exchange, so that ha4 proven.